Time in mind: a multidisciplinary review on temporal perception, cognition, and memory - Pendleton, Jeffery R. L.; Clayton, Nicola S. (Frontiers in Cognition, 2026)
This review examines temporal cognition through the lens of Mental Time Travel (MTT): the subjective experience of recalling past events and using them to construct future scenarios. The analysis specifically addresses how language and cultural context affect these abilities, integrating psychology, linguistics, cognitive neuroscience, and anthropology. Findings from comparative cognition challenge whether they are uniquely human. Although such an approach was traditionally taken in non-human primates, the field of comparative cognition has become much more diverse. Comparative insights derived from studies of corvid and cephalopod cognition are particularly pertinent, as they suggest these abilities have evolved more widely within the animal kingdom, especially in groups with very different neural architectures, raising questions about whether these abilities have evolved convergently in species undergoing similar selection pressures or independently in those subject to different selection pressures, as opposed to homologous evolution widespread amongst these animal taxa. These evolutionary perspectives inform theories of human temporal cognition and Mental Time Travel, influencing memory encoding and retrieval processes, false memory production, as well as the mechanisms underlying temporal cognition, such as episodic memory formation, interval timing, and circadian modulation of memory consolidation. Additionally, the review evaluates evidence on the cognitive impact of technological tools (calendars, clocks, and other technologies) used to externalize and standardize temporal frameworks, including implications for subjective perception and memory accuracy, and identifies directions for future interdisciplinary research. Building on this synthesis, we advance five core claims: that elements of temporal cognition likely arise under convergent evolutionary pressures; that language, culture, and social organization tune how people represent and use time; that technologies which externalize time can reshape behavior by aligning with or pulling against internally constructed event time; that memory is adaptively biased toward flexible, future-oriented construction rather than veridical record; and that these processes are structured by “mind time” and extended via transpersonal extended mental time travel, whereby shared representations support the projection and coordination of futures across individuals and generations.